2020
DOI: 10.1111/1460-6984.12584
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ultrasound in the assessment of swallowing and laryngeal function: A rapid review and critical appraisal of the literature

Abstract: Background: Ultrasound (US) is not widely used as part of the speech and language therapy (SLT) clinical toolkit. The COVID-19 pandemic has intensified interest in US as an alternative to SLT instrumental tools such as the videofluoroscopic swallowing study (VFSS), fibreoptic endoscopic evaluation of swallowing (FEES) and endoscopic evaluation of the larynx (EEL) as a non-invasive, non-aerosol-generating procedure that can be delivered at the bedside to assess swallowing and/or laryngeal function. To establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 66 publications
0
43
0
1
Order By: Relevance
“…In the UK, this led to an interest in the use of laryngeal ultrasound as a potentially safer tool. An international expert group was formed who published a rapid review of available evidence [ 31 ]. A subsequent RCSLT position statement declared that the current literature did not support ultrasound use as a stand-alone clinical swallowing assessment tool and further work would be required before it could be safely and effectively translated into clinical practice [ 32 ].…”
Section: Dysphagia Management Innovationsmentioning
confidence: 99%
“…In the UK, this led to an interest in the use of laryngeal ultrasound as a potentially safer tool. An international expert group was formed who published a rapid review of available evidence [ 31 ]. A subsequent RCSLT position statement declared that the current literature did not support ultrasound use as a stand-alone clinical swallowing assessment tool and further work would be required before it could be safely and effectively translated into clinical practice [ 32 ].…”
Section: Dysphagia Management Innovationsmentioning
confidence: 99%
“…Clinicians specializing in the upper airway currently utilize a range of invasive instrumental diagnostics (nasendoscopy; laryngoscopy; flexible endoscopic evaluation of swallowing; endoscopic evaluation of the larynx; and video fluoroscopic swallowing studies) to promote objective assessment of the biomechanics, pathology and anatomical structures involved in swallowing and laryngeal function [40][41][42][43]. The Covid-19 global pandemic challenged clinician's abilities to complete instrumental assessments, secondary to the risk of completing aerosol generating procedures affecting transmissibility of the disease [44][45][46].…”
Section: Applicability Of Laryngeal Ultrasoundmentioning
confidence: 99%
“…Although high body mass index (BMI) can impact visualization of vocal fold function [54], using laryngeal ultrasound to assess vocal fold function appears viable. Specificity, sensitivity and predictive values for vocal fold ultrasound remain variable within the literature, suggesting it could be utilized as a first line screening tool with secondary laryngoscopy for positive cases [ 43,[55][56][57][58].…”
Section: Applicability Of Laryngeal Ultrasoundmentioning
confidence: 99%
“…Ultrasound (US) has an emerging evidence base for the assessment of swallowing and laryngeal function [ 1 ]. Early research identified the ease with which anatomical landmarks and soft tissues of the upper aerodigestive tract could be identified using US [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of US as a diagnostic tool to guide therapeutic swallowing and laryngeal intervention remains underexplored. A recent rapid review in this area [ 1 ] indicated the need for further research prior to translation of US into clinical practice for this purpose. Other professional groups have started to translate US as a clinical evaluation tool [ 26 – 28 ] but a lack of sufficient evidence has hindered implementation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%